Photocatalyzed C–F Bond Heteroarylation of Trifluoromethylarenes with Heteroarenes: Two Roles of Bu3SnI as Fluoride Ion Scavenger and Activator for Photocatalyst - Sugihara, Naoki; Abe, Masayuki; Nishimoto, Yoshihiro; Yasuda, Makoto (Synthesis, 2024)
We report the C–F bond heteroarylation of trifluoromethylarenes with heteroarenes by using Ir(ppy)3 catalyst and Bu3SnI under visible-light irradiation. Various heteroarenes such as pyrrole, furan, and thiophene derivatives were applied to the present reaction. The present heteroarylation enables the transformation of various functionalized trifluoromethylarenes because of the mild reaction conditions. Notably, the late-stage transformation of a drug molecule, bicalutamide, was demonstrated. Mechanistic studies including a light on–off interval experiment, Stern–Volmer luminescence-quenching measurements, and DFT calculations clarified two critical roles of Bu3SnI for the successful progress of the heteroarylation. Bu3SnI functions as a fluoride ion scavenger to suppress the undesired C–F bond re-formation. Bu3SnI also acts as a single-electron source for the reduction of photoexcited Ir(ppy)3* to generate Ir(II) species to effectively reduce ArCF3.
Keywords: C–F bond transformation; diaryldifluoromethanes; heteroarylation; photocatalysis; organostannanes; pyrroles; furans; thiophenes